Co-operative governance in integrated development planning : local economic development in the Eastern Cape - Nelana, B. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2005.